Mengukir Identitas Budaya: Meningkatkan Branding Desa Wisata Sukarara Melalui Sukarara Songket Karnaval - Muhammad Yusril Hamzani Saputra (Pusat Kajian Pariwisata dan Publikasi Jurnal Sekolah Tinggi Pariwisata Mataram, 2023)
The Sukarara Songket Carnival is a community service activity (PKM) that serves two primary purposes: first, to promote local businesses and boost the economy of Sukarara tourism village, and second, to showcase the beauty of Songket and local culture in order to attract tourists to the area. This event takes the form of a parade featuring Sukarara's traditional costumes. The impact of the Sukarara Songket Carnival can be seen in its long-lasting effects: the event has become an annual tradition supported by the village government, it has helped to raise awareness and interest in preserving and promoting local culture, and it has increased the number of tourists visiting Sukarara, thereby improving the village's branding on a local, national, and international level.